Recent Advances in Unveiling the Role of Beta-Herpesviruses in Autoimmune Diseases - Maria Cristina Arcangeletti; Elisabetta Caselli (Microorganisms, 2021)
A dysregulated immune response can lead to recognition of self-antigens as non-self-antigens, leading to failure of the immune tolerance toward normal cells and tissues, and the consequent development of a variety of autoimmune diseases [...]